SISTEM PENDUKUNG KEPUTUSAN PADA PENJURUSAN SISWA TERKENDALA DENGAN METODE ANALYTIC HIERARCHY PROCESS - , Antonius Agung Hartono; , Widyawan, S.T., M.Sc., Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This Student concentration selection is an alternative to develop each student based on his academic skill and interest. Students with good competence of natural sciences are advised to take Natural Science (IPA) concentration, students with high knowledge of social sciences are advised to select Social Science (IPS) concentration , while students with good command of language are advised to to take Language (Bahasa) concentration. In general, the selection of student concentration at school is conducted by observing the completion of passing grade scores on certain courses that are associated with certain concentration and by taking account the concentration preference picked by each student. Student who has all passing scores on particular concentration will be advised to take such concentration. However, students with not-passing scores on his preferred concentration, the student concentration is done by concentration selection for constrained students. Concentration selection for constrained students are based on good grades of respective student on a certain concentration program. However, it often happens that concentration selection for constrained students is conducted without looking at his/her good grades. There are two factors that affect decision making process so that the decision made is not based on student's good competence, which are student's age and time constraint. Therefore, the curriculum division faces problems in monitoring the results of concentration selection for constrained students. In order to solve such problem, it is required to develop a certain Decisions Support System (DSS) on concentration selection for constrained students, which can assist the decision makers in deciding concentration for constrained students in shorter period of time and which can help the curriculum division to monitor the result of concentration selection for constrained students. The proposed DSS is developed by implementing Analytic Hierarchy Process (AHP). The testing is undertaken by comparing the result of concentration selection for constrained students done in manual way and the result obtained by developed DSS implementing AHP. For the purpose of testing, data of constrained students from X-G class of 2010/2011 school period was used. The comparison result proves that AHP in the developed DSS works well and right.